2011
DOI: 10.1016/j.cancergencyto.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic susceptibility to childhood cancer through analysis of genes in parallel

Abstract: Clinical cancer genetic susceptibility analysis typically proceeds sequentially beginning with the most likely causative gene. The process is time consuming and the yield is low particularly for families with unusual patterns of cancer. We determined the results of in parallel mutation analysis of a large cancer-associated gene panel. We performed deletion analysis and sequenced the coding regions of 45 genes (8 oncogenes and 37 tumor suppressor or DNA repair genes) in 48 childhood cancer patients who also (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Family history is still an important tool in the initiation of some referrals to cancer genetics programs and should be taken at the initial tumor diagnosis and reviewed periodically (47). However, mounting evidence supports a review of this historical referral paradigm (11)(12)(13)(14). Relying on family history alone could mean missing an early diagnosis and, therefore, the benefits of evaluation, diagnosis, and surveillance for the patient and family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family history is still an important tool in the initiation of some referrals to cancer genetics programs and should be taken at the initial tumor diagnosis and reviewed periodically (47). However, mounting evidence supports a review of this historical referral paradigm (11)(12)(13)(14). Relying on family history alone could mean missing an early diagnosis and, therefore, the benefits of evaluation, diagnosis, and surveillance for the patient and family members.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of family history in the identification of children affected by cancer predisposition has been well reported (8)(9)(10)), yet genetics evaluation can be indicated in the absence of family history, especially in the pediatric setting. Studies assessing the utility of next-generation sequencing (NGS) technologies in the detection of pediatric cancer susceptibility have revealed that family history alone does not adequately identify children with predisposition syndromes (11)(12)(13)(14). Family history will not be revealing in the setting of de novo variants or parental germline mosaicism.…”
Section: Points Of Entrymentioning
confidence: 99%
“…An inherited predisposition to cancer can be monogenic, but is also very likely to have an oligogenic aetiology in many instances (Fearnhead et al 2004; Koren-Michowitz et al 2005; Okkels et al 2006; Küry et al 2008; Wasielewski et al 2010; Martinez and Kolodner 2010; Plon et al 2011; Morak et al 2011; Gracia-Aznarez et al 2013). In amyotrophic lateral sclerosis, van Blitterswijk et al (2012a) detected FUS and TARDBP mutations in combination with ANG mutations, and C9orf72 repeat expansions with TARDBP , SOD1 and FUS mutations.…”
Section: Oligogenic Inheritance and Its Implications For Disease Penementioning
confidence: 99%
“…Advances in sequencing technology have made clinical genetic testing widely available, and large gene panels can be used to test multiple genes concurrently 3 . Many families want to know why their child developed cancer and are concerned about the risk for their other children.…”
Section: Introductionmentioning
confidence: 99%